Analisis Metode WASPAS Dalam Pemilihan Pimpinan Perusahaan - Badrul Anwar; M. Giatman; Hasan Maksum; Asyahri Hadi Nasyuha (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
The head of the company is an important figure in a business. In selecting a leader, criteria are needed that reflect a good leader. Some companies still do not use the system in selecting leaders, and even this is still nepotism, in this case the selected leaders are related to the owner of the company. A decision support system is a system that can assist in making decisions. Decision support systems are very effective in providing decisions on a problem, because this system has alternative problems and criteria according to the problems that occur. The WASPAS method in a decision support system provides the right solution for selecting prospective leaders with appropriate criteria because the WASPAS method is a unique combination of the known MCDM (Multi Criteria Decision Making) approach, namely the WSM (Weighted sum model) and the WPM weighted product model. (Weighted Product Method) initially requires linear normalization of the elements of the decision matrix by using two equations. From the results of Qi calculations using the WASPAS method, of the 6 alternatives calculated in the selection of company leaders, the best results are obtained with the highest score, namely 2.3732.